Pengaruh Periklanan Dan Kesadaran Merek Terhadap Keputusan Pembelian Sepeda Motor Merek Yamaha Pada UD. Maju Unaaha - Wahyuddin MH, Muh. (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This research was conducted to determine the effect of advertising and brand awareness on purchasing decisions for Yamaha motorcycles from UD. Forward Unaaha. This study uses a sample of 50 UD customers. Forward Unaaha. The data analysis method used is descriptive statistics and quantitative statistics, with the analysis tool used being multiple linear regression using the SPSS version 20 program package. The results showed that advertising and brand awareness simultaneously had a significant impact on purchasing decisions with a calculated F-score of 9.341 > F Table 3.195. With a T arithmetic value of 2.461 > T table 2.011, advertising sometimes has a significant influence on purchasing decisions. With a T-value of 2.095 > T-table of 2.011, brand awareness has a sometimes-significant influence on purchasing decisions.